Synthesis and characterization of Bi1.5Zn0.92Nb1.5-xSnxO6.92-x/2 pyrochlore ceramics - (:unkn) unknown (ELSEVIER SCI LTD, 2012)
The morphological, compositional, structural, dielectric and electrical properties of Bi1.5Zn0.92Nb1.5-xSnxO6.92-x/2 ceramics have been investigated by means of scanning electron microscopy (SEM), X-ray energy dispersion spectroscopy (EDS), X-ray diffraction (XRD), temperature and frequency dependent dielectric constant and temperature dependent conductivity measurements for Sn-contents in the range of 0.00 <= x <= 0.60. It was shown that single phase of the pyrochlore ceramics can only be obtained for x <= 0.25. Above this value a ZnO phase appeared in the XRD patterns and SEM micrographs as well. An increase in the lattice constant and in the temperature coefficient of dielectric constant and a decrease in the dielectric constant values with increasing Sn content was observed for the ceramics which exhibited a single phase formation. A temperature dependent but frequency invariant dielectric constant was observed for this type of ceramics. The lowest electrical conductivity and highest dielectric constant was observed for the sample which contains 0.06 Sn. The Bi1.5Zn0.92Nb1.5-xSnxO6.92-x/2 pyrochlore ceramic conductivities are thermally active above 395 K. For temperatures greater than 395 K, the conductivity activation energy which was found to be 0.415 eV for the pure sample increased to 1.371 eV when sample was doped with 0.06 Sn. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Structure and microstructure; Electrical properties; Dielectric properties; DIELECTRIC-PROPERTIES; BI1.5ZN0.92NB1.5O6.92; BEHAVIOR